Design of a Digital-Based, Multicomponent Nutrition Guidance System for Prevention of Early Childhood Obesity - Keriann H. Uesugi; Anne M. Dattilo; Maureen M. Black; Jose M. Saavedra (Hindawi Limited, 2016)
Interventions targeting parenting focused modifiable factors to prevent obesity and promote healthy growth in the first 1000 days of life are needed. Scale-up of interventions to global populations is necessary to reverse trends in weight status among infants and toddlers, and large scale dissemination will require understanding of effective strategies. Utilizing nutrition education theories, this paper describes the design of a digital-based nutrition guidance system targeted to first-time mothers to prevent obesity during the first two years. The multicomponent system consists of scientifically substantiated content, tools, and telephone-based professional support delivered in an anticipatory and sequential manner via the internet, email, and text messages, focusing on educational modules addressing the modifiable factors associated with childhood obesity. Digital delivery formats leverage consumer media trends and provide the opportunity for scale-up, unavailable to previous interventions reliant on resource heavy clinic and home-based counseling. Designed initially for use in the United States, this system's core features are applicable to all contexts and constitute an approach fostering healthy growth, not just obesity prevention. The multicomponent features, combined with a global concern for optimal growth and positive trends in mobile internet use, represent this system's future potential to affect change in nutrition practice in developing countries.